Pengembangan Media Komik Digital Untuk Meningkatkan Minat Baca Dan Hasil Belajar Siswa - Sukma Latifah; Liyana Sunanto (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The main objective of this study is to review the development and research findings concerning the implementation of digital comic-based learning media to enhance reading interest and learning outcomes among elementary school students. This study employs a Systematic Literature Review (SLR) method guided by the PRISMA 2020 protocol, consisting of journal identification, screening, eligibility assessment, inclusion, data extraction, and thematic analysis. Literature searches were conducted through reputable databases, including Google Scholar, ScienceDirect, ResearchGate, and Sinta, covering publications from 2020 to 2025. The initial search identified 1,247 studies, which were filtered according to inclusion and exclusion criteria, resulting in 15 final articles analyzed using the PICOC (Population, Intervention, Comparison, Outcome, Context) framework. The findings reveal that the use of digital comics as learning media significantly improves students’ reading interest, motivation, literacy skills, and academic performance across various subjects such as science, mathematics, language, and civic education. Furthermore, integrating local culture, Problem-Based Learning (PBL), and Education for Sustainable Development (ESD) within digital comics enhances students’ critical thinking, collaboration, and cultural literacy. However, the studies also highlight limitations such as small-scale trials, teacher readiness, and lack of technological infrastructure. Future research should focus on developing more interactive, adaptive, and culturally relevant digital comic models, incorporating augmented reality (AR) and long-term evaluation to strengthen their pedagogical impact in primary education. Keywords: digital comic, reading interest, learning outcomes, primary education, systematic literature review. Abstrak Tujuan utama penelitian ini adalah untuk menelaah perkembangan dan hasil penelitian terkait implementasi media pembelajaran berbasis komik digital dalam meningkatkan minat baca dan hasil belajar siswa sekolah dasar. Penelitian ini menggunakan metode Systematic Literature Review (SLR) dengan panduan PRISMA 2020, yang mencakup proses identifikasi, penyaringan, penilaian kelayakan, inklusi, ekstraksi data, serta analisis tematik terhadap hasil studi yang terpilih. Penelusuran literatur dilakukan melalui beberapa basis data kredibel, yaitu Google Scholar, ScienceDirect, ResearchGate, dan Sinta, dengan rentang publikasi tahun 2020–2025. Dari hasil pencarian awal sebanyak 1.247 artikel, diseleksi berdasarkan kriteria inklusi dan eksklusi hingga tersisa 15 artikel yang dianalisis lebih lanjut menggunakan kerangka PICOC (Population, Intervention, Comparison, Outcome, Context). Hasil kajian menunjukkan bahwa media komik digital berkontribusi signifikan dalam meningkatkan minat baca, motivasi belajar, kemampuan literasi, serta hasil belajar akademik siswa pada berbagai mata pelajaran seperti sains, matematika, bahasa, dan pendidikan karakter. Integrasi kearifan lokal, Problem-Based Learning (PBL), dan Education for Sustainable Development (ESD) dalam pengembangan komik digital terbukti mampu menumbuhkan kemampuan berpikir kritis, kolaboratif, dan literasi budaya siswa. Meskipun demikian, sebagian besar penelitian masih terbatas pada uji coba berskala kecil dan belum menelaah efektivitas jangka panjang serta kesiapan guru dalam penerapan media ini. Penelitian selanjutnya disarankan untuk mengembangkan model komik digital yang lebih interaktif, adaptif, dan kontekstual, serta memanfaatkan teknologi inovatif seperti augmented reality (AR) guna memperkuat efektivitas pembelajaran di sekolah dasar. Kata kunci: komik digital, minat baca, hasil belajar, sekolah dasar, systematic literature review.